Training Program to Modify Manual Wheelchairs to Simplified Power Wheelchairs for Community Dwelling Elderly People and Caregivers - Suchitporn Lersilp; Supawadee Putthinoi; Theeratorn Lersilp; Kewalin Panyo; Autchariya Punyakaew (Occupational Therapy International)
Mobility aids, particularly power wheelchairs, are necessary for elderly individuals who have health problems and disabilities. However, there is a limitation in providing power wheelchairs for such people in the community. The objectives of this study were to develop a prototype for a simplified power wheelchair and develop and evaluate a training program that has the potential to encourage evaluation and modification of the wheelchair for the elderly and their caregivers in the community. Twenty-four participants consist of elderly people and caregivers who were interested in the training program that comprised two sessions: theory and fieldwork experience. Results showed that the elderly people and caregivers, who had no knowledge or experience of wheelchair modification, were able to learn and provide suggestions for wheelchair users in their community. Two themes emerged from evaluating the training program, which included “benefits from the training program” and “improvement of the training program in the future.” Key concepts were elicited and considered in six categories: sufficient knowledge and practical learning to build confidence, values of fieldwork experiences, team support, organizational support, expansion of various contexts, and system of continued connection and services after training.